Foreign direct investment and repression: an analysis across industry sectors - Janz, Nicole (Taylor & Francis, 2018)
The impact of foreign direct investment (FDI) on repression in developing nations is still disputed. Some argue that FDI improves economic development and exports human rights values. Others criticise the exploitation of cheap labour and resources, which may lead to tensions and government oppression. Previous studies have employed aggregate FDI data, with conflicting results. Alternatively, I propose that the effects depend on what kind of FDI enters a country. I build a sectoral framework to discuss how skills and technology levels, as well as the motivation for FDI, can mediate the impact. I then examine the link in a panel data analysis (1983-2010) in 121 countries, integrating sectoral FDI in several resource, manufacturing and service industries. The results show that investment in high-skilled and -tech sectors has positive effects. The results are robust across several measures for repression, and when accounting for sector size, regional and time effects.